Influence of a herbal anticoccidial on growth, parasitological, haematological parameters and carcass traits of broilers experimentally infected with mixed field isolates of Eimeria species - SINGH, V S; PALOD, JYOTI; SHUKLA, S K; SHUKLA, P K (The Indian Journal of Animal Sciences, 2011)
An experiment was conducted to study the influence of a herbal anticoccidial powder on growth performance, parasitological, haematological parameters and carcass traits of broilers in 3 groups with 2 replicates of 20 chicks in each. Standard broiler diet without anticoccidial was fed to grA broilers while diet supplemented with herbal anticoccidial @ 6 g/kg feed without or with sodabicarb 1 g/kg to gr Band C respectively. On day 21, broilers of each group were divided into 2 sub-groups, non-infected and infected (A1-A2, B 1-B2 and C1-C2) and infected with 60,000 sporulated oocysts of mixed Einteria species.The results showed that supplemented groups B2, C2 had significant effect on postinfection growth performance, heamatological and parasitological parameters. All these parameters showed better efficacy of C2 as compared to B2. Eviscerated, giblet and spleen weights were higher in B2 and C2 than A2 while liver and pancreas weights were higher in A2. It is suggested that herbal anticoccidial with sodabicarb as a feed additive is highly effective against moderate mixed coccidial infection. Â